Politik bermoral agama : tafsir politik Hamka - Hakim, Ahmad, 1980-; Thalhah, M., 1959- (Yogyakarta : UII Press, 2005)
Political interpretation of Hamka on the relevance of Islam with politics in Indonesia.
Includes bibliographical references (p. 141-148)
Keywords: Hamka, -- 1908-1981; Muslims -- Indonesia -- Biography